Quantitative Analysis of Smooth Pursuit Eye Movement Using Video- Oculography - Hironori Fujii; Makoto Hashimoto; Kazuma Sugahara; Takuo Ikeda; Yoshinobu Hirose; Hiroshi Yamashita (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Background: Abnormalities of smooth pursuit eye movement (SPEM) are a clinical fi nding in central equilibrium disorders; the evaluation of SPEM using video-oculography (VOG) has therefore been conducted clinically in recent years. However, evaluation criteria for determining a saccadic pattern have yet to be clearly defined. The context and purpose of the study: Here, we report SPEM using VOG performed with commercially available equipment. The results were then quantitatively evaluated. Methods: Twelve patients treated at the Department of Otolaryngology at our hospital underwent SPEM testing using both electronystamography (ENG) and VOG. Eye movements were binarized using ImageJ software; these data were used for statistical analysis. Evaluation criteria included the number of saccadic eye movements, average eye movement velocity, average difference between target and eye movement velocities, and phase lag between target and eye movements. Results: We examined a healthy pattern group (n=6) and saccadic pattern group (n=6). A significant difference between the healthy and saccadic pattern groups was identified in the number of saccadic eye movements, average eye movement velocity, and average difference between target and eye movement velocities. Conclusion: Quantitative evaluation of SPEM using VOG was possible, and it facilitated the identifi cation of useful evaluation criteria. Potential implication: As SPEM testing can non-invasively evaluate brain stem and cerebellar function, screening is possible using this simple method.